ANTIDIABETIC PROPERTIES OF MUCUNA PRURIENS L. (D.C.) SEED EXTRACT AND ITS TABLET FORMULATIONS (2012)
Diabetes mellitus and its complications continue to be one of the highest causes of morbidity and mortality in recent times. Although many drugs are commercially available for use in the management of diabetes, their side effects and high costs underscore the need for new drugs. Mucunapruriens(L.) DC. (Fabaceae)is among the plants used in the management of diabetes in the tropics. The antidiabetic and ameliorative effects of the seed ethanolic extract of M.pruriens on alloxan-induced diabetes in Wistar rats were evaluated. Antidiabetic activity of the formulated M. pruriens tablets was also investigated in rabbits. Preliminary phytochemical screening of M. pruriens was done using standard methods. The effects of oral administration of the extractat doses 5.0-100.0 mg/kg body weight (bw) and glibenclamide (5.0 mg/kg bw) as standard drug were studied in alloxan-induced (120 mg/kg, i.p) diabetic rats (eight groups of six rats each, plasma glucose>450.0 mg/dL). Biochemical parameters were evaluated by spectroscopy and acute toxicity tests carried out based on mortality rate of Swiss albino mice. Tablets were formulated using direct compression and wet granulation methods. Mechanical properties of the tablets were assessed using crushing strength, friability and the crushing strength-friability ratio while drug release properties were evaluated by determining disintegration and dissolution times. The in vivo release properties of selected tablet formulations in diabetic rabbits were assessed. Data were analyzed using descriptive statistics, linear regression and ANOVA. The seed of M. pruriens contained alkaloids, saponins, steroids and phenols. The administration of 5.0, 10.0, 20.0, 30.0, 40, 50.0, and 100.0 mg/kg of the crude ethanol extract of MP led to 18.6%, 24.9%, 30.8%, 41.4%, 49.7%, 53.1% and 55.4% reduction, respectively in blood glucose level eight hours after administration, while glibenclamide resulted in 59.7% reduction. Chronic administration of the extract also resulted in significant (p<0.001) dose-dependent reduction in the blood glucose level and the alleviation of body weight loss associated with diabetes. Acute toxicity tests showed that no death was recorded after administration of the extract (0.5 –32.0 g/kg). Significantly (p<0.05) elevated levels of plasma cholesterol, triglycerides, urea, creatinine, aspartate aminotransferase and alanine aminotransferase with concomitant decrease in total protein level were observed in diabetic rats when compared with control rats. The values of these biochemical parameters were restored to normal levels by M. pruriens extract or glibenclamide after 12 weeks of treatment. Mucunapruriens tablets prepared by wet granulation exhibited higher mechanical and drug release properties than tablets prepared by direct compression (p<0.05). The tablet properties depended on the type and concentration of binders and excipients employed in the formulations. Tablets prepared by direct compression showed better reduction in the blood glucose level, compared to those prepared by wet granulation. There was a direct correlation between drug released from the tablets in vitro and its antidiabetic activity in vivo in rabbits (r2 = 0.995). Theethanolic extract of the seed of Mucunapruriens and its tablet formulations showed significant antidiabetic activity. In addition, M. pruriens displayed both hepatoprotective and cholesterol reducing properties in diabetic rats.